Adapting an anti-bullying programme for UK special schools - Badger Julia R.; Bowes Lucy; Salmivalli Christina; Hastings Richard P. (John Wiley and Sons Inc, 2025)
Bullying is a public health priority but to date, there is a lack of evidence-based anti-bullying programmes or interventions designed for use in special schools. KiVa is a successful anti-bullying programme for mainstream schools currently used in 23 countries. This brief paper outlines the co-development and adaptation of two KiVa lessons into KiVa-SEND lessons and their implementation in two special schools in the UK. One school supports pupils with a primary need of Autism, the other supports pupils with severe and complex learning disabilities. Engagement with the lessons was high from both pupils and staff; the content was perceived as acceptable by staff, complementing the curriculum and perceived as suitable for their pupils. Minor adjustments need to be made to ensure all pupils can comprehend and access the concepts. Further development of the KiVa-SEND programme and testing its potential effectiveness to reduce bullying and associated negative outcomes in special schools is now warranted.